GAMBARAN HIPOTENSI PADA PASIEN DENGAN DIAGNOSA CLOSE FRAKTUR FEMUR YANG MENJALANI TINDAKAN ORIF (OPEN REDUCTION AND INTERNAL FIXATION) DENGAN SPINAL ANESTESI MENGGUNAKAN OBAT BUPIVACAINE DAN BUPIVACAINE ADJUVAN (EPINEPHRINE) DI RSUD DR HARJONO S. PONOROGO - Al-chamdi Masfuad; Melania F. Alves Manikin; Mugia Athiyyatur Rahma; Siti Augustyaning Haqiqi; Yenisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Background: Spinal anesthesia is widely used in orthopedic surgery, particularly in open reduction and internal fixation (ORIF) procedures for femoral fractures. However, hypotension remains the most common complication due to sympathetic nerve blockade, which may compromise patient safety, especially in elderly patients. The use of adjuvant agents such as epinephrine combined with bupivacaine is expected to reduce the required dose of local anesthetic and improve hemodynamic stability. Objective: This study aimed to describe the incidence of hypotension in patients with closed femoral fractures undergoing ORIF under spinal anesthesia using bupivacaine alone compared to bupivacaine combined with epinephrine as an adjuvant. Methods: This study employed a double-blind randomized controlled trial design. A total of five ASA II patients undergoing ORIF surgery were included. Three patients received isobaric bupivacaine 20 mg combined with epinephrine 0.2 mg, while two patients received isobaric bupivacaine 20 mg alone. Hemodynamic parameters, including blood pressure, heart rate, and oxygen saturation, were monitored intraoperatively. Hypotension was defined as a decrease in mean arterial pressure (MAP) greater than 20% from baseline. Results: Hypotension occurred in three out of five patients (60%). Patients receiving bupivacaine with epinephrine tended to experience delayed onset of hypotension compared to those receiving bupivacaine alone. Elderly patients showed a higher incidence of hypotension, suggesting age as a contributing risk factor. Conclusion: The use of epinephrine as an adjuvant to bupivacaine in spinal anesthesia may provide better hemodynamic stability during ORIF surgery in patients with femoral fractures, particularly in those at risk of cardiovascular complications